2021
DOI: 10.1155/2021/6306149
|View full text |Cite
|
Sign up to set email alerts
|

An Exceedingly Rare Case of Liraglutide-Induced Liver Injury

Abstract: Liraglutide is a glucagon-like peptide-1 (GLP-1) receptor agonist used for the treatment of type 2 diabetes mellitus. We are reporting the second case of liraglutide-induced liver injury, with complete resolution of liver injury after discontinuation of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Despite the temporal association of liraglutide initiation and liver injury, DILI from glucagon-like peptide 1 agonists is rare (likelihood score E). [10][11][12][13] In large clinical trials, there was no significant difference in transaminase elevation between liraglutide and placebo. 10 Over the last decade, only single case reports of glucagon-like peptide 1 agonist hepatotoxicity exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the temporal association of liraglutide initiation and liver injury, DILI from glucagon-like peptide 1 agonists is rare (likelihood score E). [10][11][12][13] In large clinical trials, there was no significant difference in transaminase elevation between liraglutide and placebo. 10 Over the last decade, only single case reports of glucagon-like peptide 1 agonist hepatotoxicity exist.…”
Section: Discussionmentioning
confidence: 99%
“…10 Over the last decade, only single case reports of glucagon-like peptide 1 agonist hepatotoxicity exist. [10][11][12][13] One case reported liraglutideassociated autoimmune hepatitis that did not resolve with discontinuation of liraglutide and required long-term corticosteroids. 13 Otherwise, there are 2 published cases of liraglutideassociated DILI that demonstrated hepatocellular injury and resolved after discontinuing the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results that were considered irrelevant, redundant, duplicate, non-English, or related to bench research were excluded by 2 physicians. Eventually, we found only 4 articles where DILI was described in association with liraglutide use, dating from 2014 to 2021 [16][17][18][19]. All 4 articles were case reports based on individual patient experiences (level of clinical evidence: IV).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxicity improved after liraglutide cessation [18]. Parvataneni et al reported a case of liraglutide-induced DILI in a diabetic female [19]. There was complete recovery with the discontinuation of the medication [19].…”
Section: Discussionmentioning
confidence: 99%